Youth santri communication strategies to reduce uncertainty at the beginning of relationships with the opposite sex - Ihwan Agung Nugroho; Kusumajanti Kusumajanti; Aniek Irawatie (Islamic Communication Journal, 2022)
Communication between the opposite sex among Islamic boarding school students is a separate field in Islamic communication because they are governed by strict rules. This study aims to examine the communication strategies used by adolescents who are in Islamic boarding schools to reduce uncertainty at the beginning of their relationship. This study is interesting because santri are basically teenagers like teenagers in general. This study uses a quasi-qualitative method with a phenomenological approach. The research data was obtained through in-depth interviews conducted directly with six informants. The data is then analyzed by Uncertainty Reduction theory. The results of the research show that interpersonal communication is used as a strategy to reduce uncertainty. Interpersonal communication acts as a bridge of information and a means of confirming the correctness of data obtained by informants about the opposite sex, as well as bonding and enhancing closeness in relationships. This research also reveals that the basic reason for young students wanting to have a relationship is because they are curious and need someone to encourage them. This study contributes to the development of a communication strategy based on pesantren morals. The moral of the pesantren itself is one of the bases of the Islamic communication tradition.***Komunikasi antar lawan jenis dalam kalangan santri pesantren merupakan bidang tersendiri dalam komunikasi Islam karena mereka diatur oleh aturan pesantren yang ketat. Studi ini bertujuan untuk mengkaji strategi komunikasi yang digunakan oleh para remaja yang berada di dalam pondok pesantren guna mengurangi ketidakpastian pada awal hubungan mereka. Kajian ini menarik karena santri pada dasarnya adalah para remaja sebagaimana remaja pada umumnya.  Studi ini menggunakan metode quasi-kualitatif dengan pendekatan fenomenologi. Data penelitian ini diperoleh melalui wawancara mendalam yang dilakukan secara langsung kepada enam informan. Data tersebut kemudian dianalisis dengan teori Pengurangan Ketidakpastian. Hasil penelitian menunjukkan bahwa komunikasi antarpribadi digunakan sebagai strategi mengurangi ketidakpastian. Komunikasi antarpribadi berperan sebagai jembatan informasi dan sarana mengkonfirmasi kebenaran data yang diperoleh para informan tentang lawan jenisnya, juga sebagai perekat dan penambah kedekatan dalam hubungan. Studi ini juga mengungkap alasan mendasar santri remaja ingin menjalin hubungan adalah karena rasa ingin tahu dan membutuhkan sosok penyemangat. Kajian ini berkontribusi bagi pengembangan strategi komunikasi yang berbasis pada moral pesantren. Moral pesantren sendiri merupakan salah satu basis tradisi komunikasi Islam.